(untitled) (Journal of Asian Development Studies, 2025)
This study brings a novel examination of the complicated relationships among agronomical and physiological characteristics and grain yield in winter wheat, improving our awareness of how to optimize nitrogen management for sustainable crop production. The outcomes underlined that different characteristics such as leaf area index (LAI), nitrogen uptake (NUpE), photosynthetic rate (Pn), and harvest index play a significant contribution in determining grain yield. Robust positive correlations were observed between grain yield and total nitrogen content (R² = 0.92), leaf dry biomass (R² = 0.90), and photosynthetic parameters (R² = 0.94), emphasizing the critical impact of physiological efficiency in yield improvement. Outstandingly, while nitrogen application significantly enhanced chlorophyll content, carotenoids, and grain yield, excessive nitrogen input negatively impacted nitrogen use efficiency (NUE), highlighting the requirement for precision nitrogen management. This study also exhibits that better partitioning of biomass and efficient nitrogen allocation to grains (N harvest index) are significant drivers of yield strength and improvement. These outcomes advance in relating physiological characteristics through agronomical operations, offering wheat breeders and agronomists valuable approaches for boosting yield potential while reducing environmental impact. This research covers how to increase nitrogen-efficient and high-yielding wheat genotypes, which are important for resolving worldwide food safety problems and sustainable agriculture.